The role of neutrophil/lymphocyte ratio (NLR) and platelet/lymphocyte ratio (PLR) in the early diagnosis of pulmonary mucoepidermoid carcinoma and their clinical significance: NLR and PLR in pulmonary mucoepidermoid carcinoma - Yang, Limin; Zhao, Cuicui; Lei, Wei (Journal of Medical Biochemistry, 2025)
Objective: Pulmonary mucoepidermoid carcinoma (PMEC) is often misdiagnosed due to the lack of specificity of clinical symptoms. The ratio of neutrophil/lymphocyte ratio (NLR) and the ratio of platelet/lymphocyte ratio (PLR) are used in the diagnosis and prognostic assessment of a variety of diseases. This paper aims to verify the auxiliary diagnostic value of NLR and PLR in peripheral blood of PMEC, and calculate several indexes to confirm the reliability of the hypothesis. Methods: A total of 26 patients with PMEC were enrolled as case group and 156 healthy patients were selected as the control group in this study according to the inclusion criteria and exclusion criteria. All clinical data were collected and all subjects took blood from fasting veins. The correlation analysis of NLR, PLR and tumor indicators were consistent with the normal distribution using Pearson analysis. The receiver operating characteristic (ROC) curve was used to calculated the diagnostic value of NLR and PLR. Results: NLR and PLR levels were significantly increased in patients with PMEC compared with healthy controls (***P<0.001). PLR was positively correlated with the patient’s stage [95% confidence interval (CI): 0.3408-0.7434; r=0.4590, P<0.05], and NLR was independent of the patient’s stage in PMEC patients [95% CI:-0.1510-0.6479 ; r=0.3002, P>0.05]. NLR was positively correlated with the patient’s tumor size [95% CI:0.1929-0.7821; r=0.5532, P<0.05], and PLR was independent of the patient’s tumor size [95% CI:-0.1298-0.6199 ; r=0.2887, P>0.05]. ROC curve analysis showed that NLR and PLR could be used as diagnostic indicators to distinguish patients with PMEC from normal people. Conclusion: NLR and PLR tests are simple, non-invasive, inexpensive and with high patient compliance. As potential markers for screening PMEC patients, NLR and PLR have auxiliary value for further exploration and research, and are worth promoting in the clinical setting.